Asuhan Keperawatan Pada Pasien Tn.A Dengan Congestive Heart Failure - Firly Rahmatiana; Hertuida Clara (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2019)
CHF or Congestive Heart Failure is a clinical syndrome or a set of signs and symptoms are characterized by shortness of wicked breath and fatik ( at nest or during activity). This cause by the inability of the heart to pump blood throughout the body, due to structural and functional disordes of the heart. Moreover, signs and symptoms will be found like shortness of breath at rest or during activity, feeling tired, not powerful, water retention such as pulmonary congestion. Leg edema, and abnormalities of heart structure and function (Marulam M, 2015). According to LeMone (2012), the consequences of heart failure quickly affect the lack of blood supply, thus causing cell death due to lack of oxygen carried in the blood it self. The goals of this research is to get real experience in nursing care for the patient. The method in this research is descriptive method or description of a case. The nursing problems in the form of cleaning the airway is not effective, in effective airway clearence associated with increased sputum production, decreased cardiac output associated with changes in myocardial contractility, structural changes, excess fluid volume is associated with retention. Four nursing diagnoses have not been resolved because congestive heart disease is an end-stage heart disease that is irreversible where the heart will not be able to recover as before